Glass transitions in native silk fibres studied by dynamic mechanical thermal analysis. Issue 27 (20th June 2016) - Guan, Juan; Wang, Yu; Mortimer, Beth; Holland, Chris; Shao, Zhengzhong; Porter, David; Vollrath, Fritz
Abstract : Silks are a family of semi-crystalline structural materials, spun naturally by insects, spiders and even crustaceans. Abstract : Silks are a family of semi-crystalline structural materials, spun naturally by insects, spiders and even crustaceans. Compared to the characteristic β-sheet crystalline structure in silks, the non-crystalline structure and its composition deserves more attention as it is equally critical to the filaments' high toughness and strength. Here we further unravel the structure–property relationship in silks using Dynamic Mechanical Thermal Analysis (DMTA). This technique allows us to examine the most important structural relaxation event of the disordered structure the disordered structure, the glass transition (GT), in native silk fibres of the lepidopteran Bombyx mori and Antheraea pernyi and the spider Nephila edulis . The measured glass transition temperature T g, loss tangent tan δ and dynamic storage modulus are quantitatively modelled based on Group Interaction Modelling (GIM). The "variability" issue in native silks can be conveniently explained by the different degrees of structural disorder as revealed by DMTA. The new insights will facilitate a more comprehensive understanding of the structure–property relations for a wide range of biopolymers.